2021
DOI: 10.1186/s12913-021-07309-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends of chronic illness in emergency department admissions among elderly adults in a tertiary hospital over ten years

Abstract: Background This study aimed to determine to what extent an aging population and shift to chronic illness has contributed to emergency admissions at a tertiary care hospital over ten years. Methods This was a retrospective observational study performed using a database of all emergency admissions from the Emergency Department (ED) at a single tertiary hospital in Singapore during a ten-year period (January 1st, 2008 to December 31st, 2017). Emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Emergency admission is de ned as patients visiting the department of cardiology by emergency admitted for inpatient care. [23] Older patients are more likely to have a longer LOS after emergency admissions. [24] The admission type has the highest importance and studies have shown that emergency admission was associated with longer LOS in patients in cardiac units.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency admission is de ned as patients visiting the department of cardiology by emergency admitted for inpatient care. [23] Older patients are more likely to have a longer LOS after emergency admissions. [24] The admission type has the highest importance and studies have shown that emergency admission was associated with longer LOS in patients in cardiac units.…”
Section: Discussionmentioning
confidence: 99%
“…5 The Australian E-Health Research Centre, Commonwealth Scientific and Industrial Research Organisation, Brisbane, Australia. 6 Queensland Ambulance Service, Queensland Government, Brisbane, Australia. 7 Gold Coast University Hospital, Gold Coast, Australia.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Globally, emergency departments are overcrowded and unable to meet an ever-increasing demand for healthcare [1]. The increasing demand for emergency care services is a significant challenge for healthcare systems worldwide [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%